ChemInform Abstract: Iron‐Catalyzed [4C + 1N] Cyclization of 4‐Acetylenic Ketones with Primary Amines: Synthesis of 5‐(Aryl)alkylidene‐4, 5‐dihydropyrroles. Issue 17 (April 2015) - Sun, Bo; Ma, Quan; Wang, Yeming; Zhao, Yuegang; Liao, Peiqiu; Bi, Xihe
Abstract An environmentally friendly route towards fully substituted 4, 5‐dihydropyrroles is provided.